Effect of Chicken Egg Shell Powder Solution on Microhardness of Artificially Induced Cemental Erosion: An In vitro Study - Lembai, Sneha; Mathew, Josey; George, Liza; Charlie, K. M.; Padavil, Tobin C.; Rajan, Rishi (Kerala Dental Journal, 2025)
Abstract Context Root caries is a significant problem among aging adults. The chicken egg shell powder (CESP) derived from chicken eggshells has demonstrated efficacy in remineralising the enamel affected by carious lesions. This study tried to assess remineralisation potential of CESP on cementum. If proven effective, may be used for management of root caries. Aims This study aims to evaluate and compare the effect of treating cementum with CESP for different time intervals in comparison with casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) using Vickers microhardness test. Settings and Design In vitro. Subjects and Methods CESP solution was prepared. Cervical third of root of 32 mandibular molars were sectioned to obtain 5 mm thick sections. For inducing cemental erosion, teeth were submerged in six ml of carbonated beverage. Samples were randomly allotted into four groups (n = 8): Group I (Control): untreated (sample immersed in deionised water), Group II: CPP-ACP was applied daily using an applicator tip for 4 min over a period of 7 consecutive days, Group III: Immersed in CESP solution 2 times a day (30 min) for seven consecutive days and Group 1V: Immersed in CESP solution for 7 consecutive days. Analysis of microhardness done for normal cementum, following initiation of dental erosion and after 7 days following remineralisation using Vickers microhardness test. Statistical Analysis Used For intragroup comparison, paired t-test and one-way ANOVA was utilised. Post hoc analysis was employed to validate differences observed between groups. Results The results suggested that mean increase in microhardness of teeth treated with CPP ACP was greater than those immersed in CESP for continuous 7 days, followed by teeth immersed in CESP 30 min twice daily. No significant difference was seen in mean value among remineralised groups (P = 0.59). CESP at various time intervals showed equivalent result of remineralisation compared to CPP-ACP. Conclusions CESP being natural, economic and easy to use can be used as an alternative to present day remineralising agents such as CPP-ACP. The outlook appears promising for the prevention and treatment of cemental erosion.